How significant is cost-shifting behavior under the diagnosis intervention packet payment reform? Evidence from the coronary heart disease market - Tan, Huawei; Zhang, Xueyu; Bi, Shengxian; Chen, Yingchun; Guo, Dandan (Frontiers in Public Health, 2024)
BackgroundControlling the growth of inpatient costs presents a major challenge in China’s healthcare system. China introduced a new case-based payment method, the “Diagnosis Intervention Packet” (DIP), to address the surge in hospitalization expenses. However, the influence of DIP payment reform on cost shifting among coronary heart disease (CHD) inpatients remains unclear.MethodsThis study focused on Zunyi, a national pilot city for DIP, utilizing inpatient claim data to assess the effects of DIP payment reform. We analyzed the influence on total health expenditures (THE), individual payments excluding reimbursement (IPER), proportion of IPER, copayments for category-B, proportion of copayments for category-B, copayments for category C, and proportion of copayments for category C per case for CHD inpatient.ResultsResults indicate a significant reduction in THE per case for CHD inpatients after the DIP reform (β = −0.1272, p < 0.01). Increases in cost shifting were observed in IPER (β = 0.1080, p < 0.05), the proportion of IPER (β = 0.0551, p < 0.01), copayments for category B (β = 0.2392, p < 0.01), and the proportion of copayments for category B (β = 0.0295, p < 0.01), along with the proportion of copayments for category C (β = 0.0255, p < 0.01). However, the copayments for category C did not significantly change. Notable variations in the effects of cost control and shifting were observed across different hospital categories, teaching statuses, hospital grades, and ownership types.ConclusionThe DIP reform significantly reduced the THE per case for CHD inpatients, while shifting in-policy expenditures to IPER, particularly with a greater shift intensity in the proportion of Class B compared with the proportion of Class C.